“Needless People” of the 21st Century as a problem of urban studies and not only - Maxim Privalov (Проект Байкал, 2018)
The article speaks about the necessity of comprehension of the socio-cultural consequences of the fourth industrial revolution, the total robotization and the expansion of artificial intellectual systems and networks. It underlines the progressing displacement of humans from the economics, the consistent dehumanization of the society, mass technological unemployment and emergence of the numerous class of “needless people”. The author forecasts the impact of these processes on the transformation of the economic structure, the reformatting of the social problems, as well as the spatial environment and the functions of the cities. He comes to the conclusion that the “needless people” phenomenon will be of paramount importance for the societies of the 21st century.